Extracorporeal Membrane Oxygenation as Salvage Therapy in the Peripartum Period: A Case Series. Issue 7 (July 2020) - Patel, Sameer; Loveridge, Robert; Willars, Chris; Vercueil, Andre; Best, Thomas; Auzinger, Georg
Abstract : Despite considerable advances in maternity care, maternal death rates remain unacceptably high. Even with optimal care, unexpected complications can result in catastrophic consequences. Hemorrhage, cardiovascular and coronary conditions, and cardiomyopathy make up the three most common causes of pregnancy-associated deaths, followed by sepsis and thromboembolic disease. Although a number of deaths may be deemed to be potentially avoidable with appropriate education and infrastructure, others such as refractory hypoxia and peripartum cardiomyopathy are not. All possible interventions should be explored, including the use of more novel and aggressive life support technologies, such as extracorporeal membrane oxygenation. We report the successful use of extracorporeal membrane oxygenation in three cases of severe peripartum morbidity. The first case describes spontaneous coronary artery dissection supported with veno-arterial extracorporeal membrane oxygenation for refractory cardiogenic shock after out-of-hospital cardiac arrest. The second is a case of severe pregnancy-related liver disease bridged to emergency liver transplantation with veno-venous extracorporeal membrane oxygenation. Finally, we report the use of extracorporeal cardiopulmonary resuscitation for refractory cardiac arrest in a postpartum patient. Peripartum extracorporeal membrane oxygenation is feasible in carefully selected patients, and should be considered early when conventional therapy is failing, or as a salvage rescue therapy when it has failed.